Currency Depreciations in Emerging Economies: A Blessing or a Curse for External Debt Management? - Boris Fisera; Menbere Workie Tiruneh; David Hojdan (Charles University in Prague, Institute of Economic Studies (IES), 2021)
We investigate the long-term effect of domestic currency depreciation on the external debt for a panel of 41 emerging economies over the years 1999-2019. Using heterogenous panel cointegration methods, we find that domestic currency depreciation leads to an increase in external debt to GDP ratio over the long-term and it reduces the sustainability of external debt. This is particularly the case for larger depreciations, while smaller depreciations might reduce the external debt burden over the long-term for more developed emerging economies. Poorer emerging economies face a greater increase in external debt burden following domestic currency depreciation. We also find that higher exchange rate volatility and the use of floating exchange rates contributes to an increase in external debt burden over the long-term. Consequently, our results suggest that for emerging economies, having more volatile and floating exchange rates reduces the sustainability of external debt. We find asymmetrical effects of exchange rate depreciation on external debt: higher central bank independence limits the effect of currency depreciation on external debt, while higher financial development and illicit financial flows augment the effect of depreciation on external debt.
Keywords: E50; F31; F34; 330; external debt; exchange rate; currency depreciation; exchange rate volatility; exchange rate regime; DFE estimator; PMG estimator